COMPARISON OF CLINICAL EFFICACY AND SIDE EFFECTS OF LEVONORGESTREL IMPLANTS VERSUS COPPER T IUCD: A SIX-MONTH STUDY - Akbar, Amina; Adila Anwar; Shakra Tabasam; Afroze, Sadaf; Shahid, Ghana; Shehnaz Sheeba (Journal of Ayub Medical College Abbottabad, 2025)
Background: This study examines long-term contraceptives, specifically comparing levonorgestrel implants and copper IUCDs, focusing on their effectiveness and side effects. The goal was to evaluate the performance and acceptance of Levonorgestrel implants versus copper IUCDs, documenting side effects for each method. Methods: Conducted at the Obstetrics & Gynecology Departments of PAF Hospital Islamabad and PAF Hospital, Kamra from December 2023 to May 2024. The study enrolled women opting for levonorgestrel implants or copper IUCDs. Out of an intended study sample of 166, 145 women aged 20-40 participated. Those using other contraceptives or with medical contraindications were excluded. Follow-ups over six months collected data on side effects and demographics, analyzed with SPSS-22, considering p s 0.05 significant. Results: Among 145 women, primarily 26-30 years old, those with lUCDs reported more prestudy menstrual irregularities (83.3%) than Levonorgestrel implant users (61.7%). Levonorgestrel implants resulted in fewer side effects like dysmenorrhea and headaches. Conclusion: Levonorgestrel implants and copper IUCDs are both effective at preventing pregnancy. Levonorgestrel implants, however, led to fewer side effects such as menstrual changes and weight gain, favoring its use. Both methods maintained high satisfaction after six months.